2006
DOI: 10.1093/annonc/mdl042
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of the humanized monoclonal anti-epidermal growth factor receptor (EGFR) antibody EMD 72000 (matuzumab) in combination with paclitaxel in patients with EGFR-positive advanced non-small-cell lung cancer (NSCLC)

Abstract: Matuzumab doses up to 800 mg weekly with paclitaxel 175 mg/m(2) every 3 weeks are well tolerated, with no apparent drug interactions and with evidence of antitumor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 20 publications
2
52
0
2
Order By: Relevance
“…Phase I trials showed well-tolerated antitumor activity, inhibition of phosphorylated EGFR and effect of receptor-dependent signaling and transduction; effects were seen even in the lowest-dose group (Graeven et al, 2006;Kollmannsberger et al, 2006). HER-2/neu is overexpressed in 25-30% of invasive breast cancer and is associated with poor disease-free survival.…”
Section: Naked Antibodiesmentioning
confidence: 99%
“…Phase I trials showed well-tolerated antitumor activity, inhibition of phosphorylated EGFR and effect of receptor-dependent signaling and transduction; effects were seen even in the lowest-dose group (Graeven et al, 2006;Kollmannsberger et al, 2006). HER-2/neu is overexpressed in 25-30% of invasive breast cancer and is associated with poor disease-free survival.…”
Section: Naked Antibodiesmentioning
confidence: 99%
“…The results from the phase I portion of this study, including patients treated with the 200-, 400-, and 800-mg doses of matuzumab, were previously published (13). In our patient cohort, including 23 eligible patients from the phase I/II, clinical activity was seen in 61% (14/23) of patients, including one complete response (CR, 1/23, 4%), three partial responses (PR, 3/23, 13%), and 10 cases with stable diseases (SD, 10/23, 44%) as defined by Response Evaluation Criteria In Solid Tumors (RECIST) criteria for at least two cycles of therapy [as assessed by computed tomography (CT) imaging].…”
Section: Patient Cohortmentioning
confidence: 99%
“…Matuzumab (13), cetuximab (14), and ABX-EGF (15) have proven to be effective in clinical studies enrolling patients with a variety of EGFR-expressing tumors. Recent in vitro data suggest that cetuximab potently targets TKI-sensitive as well as resistant EGFR TK mutant isoforms (16 -18), but substantial differences are observed in clinical response rates (14).…”
Section: Introductionmentioning
confidence: 99%
“…In recent phase I studies of chemotherapy plus matuzumab in lung and pancreatic cancer (at doses ranging from 100 to 800 mg weekly), the MTD was not reached although one DLT of grade 4 neutropaenia was observed at matuzumab 800 mg combined with paclitaxel. Antitumour activity was reported and pharmacodynamic data revealed blockade of the EGFR pathway (Graeven et al, 2006;Kollmannsberger et al, 2006). Preliminary data of the phase I study of PFL (cisplatin, leucovorin and 5FU) and matuzumab (at doses of 400 or 800 mg weekly) in advanced OG cancer indicate good tolerability at the 400 mg dose level (DL) (Trarbach et al, 2005).…”
mentioning
confidence: 99%